Effects of static and progressively increasing prey density regimens on larval performance of largemouth bass (Micropterus nigricans) reared in an intensive recirculating aquaculture system - Nelson S. Parajuli; Robert Glennon; Anneleen Swanepoel; Dustin Goodman; Josh Sakmar; Allen Nicholls; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Ian A.E. Butts (Aquaculture, 2027)

Cattle behavior classification using Hidden Markov Models - Thomas Lipinski; Ali Yalcin; Noah G. Davis; Samuel A. Wyffels; Timothy DelCurto (Computers and Electronics in Agriculture, 2026)

Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

An interactive tool to identify existing evidence and research gaps on agricultural production processes to address heavy metals in foods: developed from a scoping review - Rupal Trivedi; Lauren E. O’Connor; Cassi N. Leta; Trish J. Bosse; Julie S. Davis; Arin A. Balalian; Rachel C. Thoerig; Shailesh M. Advani; Margaret J. Foster; Kyle M. Holland; David D. Baltensperger; Delbert M. Gatlin III; et al. (Critical Reviews in Food Science and Nutrition, 2026)

A Model for Clinician and Staff Education in the Engagement of American Indians in Genomic Research - Ursa Brown-Glaberman; Alissa Greenbaum; Koby Blackwater; Raven Chavez; Cindy K. Blair; Jude Khatib; Jacklyn Nemunaitis; V. Shane Pankratz; Bethany Davis; Jill Peters; Kelsey Pettes; Mallery Quetawki; et al. (Journal of Cancer Education, 2026)
Despite notable differences in cancer incidence and outcomes, fewer American Indians have participated in cancer research and genomic testing relative to their population size. Contributing factors include historical scientific mistrust, lack of culturally appropriate research methodologies, and limited access. With the launch of a cancer genomic sequencing trial in American Indians from the Southwestern United States (US), clinicians and staff encountered challenges engaging patients, recognizing the complexity of research in this population. We describe a novel approach to educate study team members regarding genomic cancer testing and research in American Indian populations. Clinical faculty and staff investigators participated in (1) hands-on experiential workshops related to core beliefs and healthcare in American Indians and (2) the development of provider-facing educational materials. After participation in the workshops, investigators, including American Indian researchers, created two sets of provider-facing materials and implemented them in clinic. The first provided a summary detailing trial eligibility, procedures, and privacy safeguards. The second outlined topics fostering respectful engagement of American Indians in research, outlining core beliefs including the importance of family and community in decisions, a framework of inherent cycles in human life and nature, the importance of visual aids, and the complementary nature of traditional healing. An approach incorporating cultural training for clinicians and staff is feasible when engaging American Indians of the Southwestern US in genomic research. This methodology may serve as a model for future initiatives to engage with American Indians in cancer research and in both clinical and research related genomic testing.

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Investigating the Impact of Blunt Force Trauma: A Probabilistic Study of Behind Armor Blunt Trauma Risk - Vivek Bhaskar Kote; Lance L. Frazer; Zachary S. Hostetler; Derek A. Jones; Matthew Davis; Joost Op’t Eynde; Jason Kait; Derek Pang; Dale Bass; Jared Koser; Alok Shah; Narayan Yoganandan; et al. (Annals of Biomedical Engineering, 2026)

From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Effects of different soybean protein sources on growth performance, feed utilization efficiency, intestinal histology, and physiological gene expression of Pacific white shrimp (Litopenaeus vannamei) in green water and indoor biofloc system. - Khanh Q. Nguyen; Aya S. Hussain; Adela N. Araujo; Leila M. Strebel; Trenton L. Corby; Melanie A. Rhodes; Timothy J. Bruce; Jorge Cuéllar-Anjel; D. Allen Davis (Aquaculture, 2026)

Evaluation of phytogenic product supplementation on the growth performance, immune function, and gut microbiota composition in fingerling channel catfish (Ictalurus punctatus) - Ishini A. Appuhami; D. Allen Davis; Yoonhang Lee; Abdulmalik A. Oladipupo; Brent M. Vuglar; Fernando Y. Yamamoto; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2026)

Bacterial community formation on plastic and glass in coral reefs - Yusuke Iwaki; Kohei Hamamoto; Fabian Gösser; Chengze Li; Jeffrey Jolly; Sen-Lin Tang; Timothy Ravasi; James Davis Reimer (Coral Reefs, 2025)

Comparison and efficacy of soy-based ingredients in practical diets for Florida pompano (Trachinotus carolinus) - Trenton L. Corby; Trinh H. V. Ngo; Khanh Q. Nguyen; Adela Araujo; Leila Strebel; Stephanie Velasquez; Melanie Rhodes; Timothy J. Bruce; Marty Riche; D. Allen Davis (Aquaculture International, 2025)
Three Trials were performed to understand better how soy processed in different ways impacts the growth, feed conversion ratio, and health of the Florida pompano ( Trachinotus carolinus ). The first two growth Trials were performed to evaluate the efficacy of an open soy-based diet compared to a commercially produced, fish meal (FM)–based diet. Trial 1 compared a soy-based diet to a commercial FM-based diet using juvenile fish (23.2 ± 1.87 g) across six replicates over 42 days. The FM-based diet significantly outperformed the soy diet in final biomass ( p = 0.026), weight gain ( p = 0.006), and feed conversion ratio (FCR) ( p = 0.015). Trial 2 used larger fish (38.1 ± 0.86 g) with three replicates over 56 days and found no significant differences between diets. Histological samples of the distal intestine showed no statistical differences in symptoms conducive to soy-induced enteritis between the practical soy diet and the commercial FM diet. Trial 3 evaluated nine experimental soy-based diets in juvenile pompano (4.82 ± 0.09 g) across quadruplicate tanks for 76 days. The basal diet containing 49.97% solvent-extracted soybean meal (SBM) was compared with diets where SBM was replaced at 50% or 100% with low oligosaccharide SBM, soy protein concentrate, or enzyme-treated SBM, or at 25% or 50% with expeller-extruded SBM. No significant differences were found in weight ( p = 0.493), survival ( p = 0.925), or FCR ( p = 0.874). Histological analysis showed no adverse intestinal effects in lamina propria thickness, lamina propria cellularity, connective tissue thickening, or abundance of goblet cells.

Genotoxicity evaluation of ten nitrosamine drug substance-related impurities using 2D and 3D HepaRG cell models - Ji-Eun Seo; Hannah Xu; Xilin Li; Aisar H. Atrakchi; Timothy McGovern; Karen L. Davis Bruno; David A. Keire; Nan Mei; Robert H. Heflich; Xiaoqing Guo (Regulatory Toxicology and Pharmacology, 2025)

Evaluation of processed soy ingredients for largemouth bass (Micropterus nigricans) fingerlings on growth performance, intestinal health, and disease susceptibility - Jamison L. Semla; Ian A.E. Butts; D. Allen Davis; Abdulmalik A. Oladipupo; Benjamin R. LaFrentz; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Comparative DNA damage induced by eight nitrosamines in primary human and macaque hepatocytes - Ji-Eun Seo; Xiaobo He; Matthew Bryant; Aisar H. Atrakchi; Timothy J. McGovern; Karen L. Davis Bruno; Robert H. Heflich; Xiaoqing Guo (Chemico-Biological Interactions, 2025)

Investigation of dietary exogenous protease and humic substance on growth, disease resistance to Flavobacterium covae and immune responses in juvenile channel catfish ( Ictalurus punctatus ) - Abdulmalik A. Oladipupo; Anita M. Kelly; D. Allen Davis; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Many bacterial pathogens impact the US catfish industry, and disease control can be challenging for producers. Columnaris disease in channel catfish, Ictalurus punctatus , is primarily caused by Flavobacterium covae (formerly F. columnare ). Immunostimulants may enhance nonspecific immune responses and offer an alternative to antibiotic treatments in catfish. Furthermore, dietary protein sources and inclusions are also essential to fish health and nutrition and may enhance overall fish performance in pond culture. The current project evaluated two immunostimulants: a protease complex (PC) and a humic substance (HS) derived from a reed‐sedge peat product. A 60‐day trial examined the effects of five diets on growth performance, immune response and resistance to experimental F. covae infection in channel catfish. Diets included a high‐quality fishmeal diet (32%; CF32), a high‐protein soy‐based diet (32%; C32), a low‐protein soy‐based diet (28%; C28; predominately used in industry), a low‐protein soy diet supplemented with C28 + PC at 175 g metric ton −1 and C28 + HS in a low‐protein diet at 23 g metric ton −1 . Following feeding for 60 d, juvenile channel catfish were sampled for growth performance and baseline health indicators ( n = 3; body mucus, blood for sera, kidney and spleen). A subset of fish was then subjected to an immersion‐based in vivo challenge trial with F. covae (ALG‐00‐530; 10 6 CFU mL −1 exposure). At 60d post‐initiation, there were no dietary differences in the relative growth rate ( p = .063) or thermal growth coefficient ( p = .055), but the 32% diets generally appeared to perform best. Post‐challenge, the C32 group's mortality was higher than the C28 + PC ( p = .006) and C28 + HS diets ( p = .005). Although not significant, the C28 and CF32 groups also demonstrated higher mortality compared to both PC and HS diets. Sera lysozyme concentration was found to increase following pathogen challenge ( p p il‐1β , il‐8 , tnf‐α and tgf‐β ) were observed at trial midpoint and post‐infection when compared to 60d. The C28 treatment was found to have lower tnf‐α expression than the C28 + PC ( p = .042) and C28 + HS ( p = .042) groups following exposure to F. covae . These challenge data suggest that the immunostimulants (PC and HS) in plant‐based protein may be beneficial in protecting against F. covae when offered in low‐protein channel catfish diets.

Influence of dietary fermented yeast products (Saccharomyces cerevisiae) on performance, health and microbiome of Nile tilapia (Oreochromis niloticus) and the influence of discharge water in the production of romaine lettuce (Lactuca sativa) - Uthpala M. Padeniya; D. Allen Davis; Daniel E. Wells; Courtney E. Harrison; Benjamin R. LaFrentz; Benjamin H. Beck; Luke A. Roy; Mark Farmer; Timothy J. Bruce (Animal Feed Science and Technology, 2025)

Utilization of different protein sources and intestinal histology in yellowtail snapper, Ocyurus chrysurus - Stephanie F. Velasquez; Leonardo Ibarra-Castro; John D. Stieglitz; Khanh Nguyen; Timothy J. Bruce; D. Allen Davis (Animal Feed Science and Technology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Assessment of different dietary soybean meals and corn fermented protein in practical diets for fingerling channel catfish. - Abel R. Paladines-Parrales; Khanh Q. Nguyen; Magida Tabbara; Uthpala Padeniya; Abigeal Adeyemi; Yoonhang Lee; Timothy J. Bruce; D. Allen Davis (Animal Feed Science and Technology, 2025)

Vertebrates in trade that pose high invasion risk to the United States - Wesley M. Daniel; Helen R. Sofaer; Catherine S. Jarnevich; Richard A. Erickson; Brett A. DeGregorio; Peder S. Engelstad; Jonathan Freedman; Susan Canavan; E.M. Dean; Michael J. Adams; Charmayne L. Anderson; Mindy Barnett; et al. (Biological Conservation, 2025)

Delineation of outbreak stages of the coral-killing sponge Terpios hoshinota - Britta Katharina Fiedler; Anthony David Montgomery; Fiona Chong; Hiromu Miyagi; Marilyn Carletti; Rocktim Ramen Das; Yoko Shintani; Timothy Ravasi; James Davis Reimer (Regional Studies in Marine Science, 2024)

Mutagenicity and genotoxicity evaluation of 15 nitrosamine drug substance-related impurities in human TK6 cells - Xilin Li; Yuan Le; Xiaoqing Guo; Sruthi T. King; Robert T. Dorsam; Aisar H. Atrakchi; Timothy J. McGovern; Karen L. Davis-Bruno; David A. Keire; Robert H. Heflich; Nan Mei (Regulatory Toxicology and Pharmacology, 2024)

Optimizing the detection of N-nitrosamine mutagenicity in the Ames test - Robert H. Heflich; Michelle E. Bishop; Roberta A. Mittelstaedt; Jian Yan; Sharon K. Guerrero; Audrey M. Sims; Kamela Mitchell; Nyosha Moore; Xilin Li; Nan Mei; Rosalie K. Elespuru; Sruthi T. King; et al. (Regulatory Toxicology and Pharmacology, 2024)

Assessment of dietary yeast‐based additives for cultured catfish and tilapia health - Guillaume Cacot; D. Allen Davis; Benjamin R. LaFrentz; Mark R. Liles; Ian A. E. Butts; Craig A. Shoemaker; Benjamin H. Beck; Mark Farmer; Timothy J. Bruce (Journal of Fish Diseases, 2024)
Channel catfish ( Ictalurus punctatus ) and Nile tilapia ( Oreochromis niloticus ) are two aquaculture species of great importance. Intensive production is often hindered by poor growth performance and disease mortality. The aim of this study was to evaluate the potential of a commercial fermented yeast product, DVAQUA, on channel catfish and Nile tilapia growth performance metrics and disease resistance. Channel catfish and Nile tilapia were fed practical diets supplemented with 0%, 0.1% or 0.4% of DVAQUA over approximately 2‐month feeding periods in recirculation aquaculture systems. To assess the potential of the postbiotic against common aquaculture pathogens, juvenile catfish were subsequently challenged by immersion with Edwardsiella ictaluri S97‐773 or virulent Aeromonas hydrophila ML09‐119. Nile tilapia juveniles were challenged by injection with Streptococcus iniae ARS‐98‐60. Serum lysozyme activity, blood chemistry and growth metrics were measured at the end of the feeding period, but no differences were observed across the different metrics, except for survival. For the pathogen challenges, there were no differences in endpoint mortality for channel catfish with either pathogen ( p > .05). In contrast, Nile tilapia survivability to S. iniae infection increased proportionally to the inclusion of DVAQUA ( p = .005). Changes to sera lysozyme activity were also noted in the tilapia trial, with a reduction of activity in the fish fed the 0.4% DVAQUA diet compared to the control diet ( p = .031). Expression profiles of proinflammatory genes and antibodies were also found to be modulated in channel catfish fed the postbiotic, indicating some degree of protective response. These results suggest that this postbiotic may be beneficial in protecting Nile tilapia against S. iniae infection by influencing immune parameters and additional research is needed to evaluate the potential of this DVAQUA for improving catfish health and disease control.

Repeat treatment of organotypic airway cultures with ethyl methanesulfonate causes accumulation of somatic cell mutations without expansion of bronchial-carcinoma-specific cancer driver mutations - Yiying Wang; Yuan Le; Kelly L. Harris; Ying Chen; Xilin Li; Jennifer Faske; Rebecca A. Wynne; Roberta A. Mittelstaedt; Xuefei Cao; Jaime Miranda-Colon; Lana Elkins; Levan Muskhelishvili; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Local Watershed Properties Cannot Explain Divergent Dynamics of Pacific Herring in an Urbanizing Estuary - Leah R. Davis; Fabienne Urfer; Timothy E. Essington; Blake E. Feist; Tessa B. Francis (Estuaries and Coasts, 2024)
Pacific herring ( Clupea pallasii ) is a foundational species in Puget Sound (Washington State, U.S.A.) and is subject to many anthropogenic threats. We assessed the overall status of the Puget Sound Pacific herring sub-stock complex and asked whether watersheds with less urban or agricultural land cover, less impervious surface, and lower human density were associated with better stock status. To this end, we developed multiple metrics of sub-stock population status; characterized watershed properties with respect to land use/land cover, percent impervious surfaces, and human density; and used statistical model selection to evaluate the weight of evidence in support of our hypotheses. Overall, the status of sub-stocks was poor; metrics for most sub-stocks indicate a decline from 1996–2021. However, the status metrics of sub-stocks were not related to recent (2016) watershed characteristics or the rate of change in watershed characteristics from the mid-1990s to 2016. While the cumulative effects of local human land use throughout Puget Sound may be contributing to the deterioration of spawning biomass, these results also suggest that other drivers that operate at larger scales (e.g., predation, disease, climate) are likely important.

Mouse phenome database: curated data repository with interactive multi-population and multi-trait analyses - Molly A. Bogue; Robyn L. Ball; David O. Walton; Matthew H. Dunn; Georgi Kolishovski; Alexander Berger; Anna Lamoureux; Stephen C. Grubb; Matthew Gerring; Matthew Kim; Hongping Liang; Jake Emerson; et al. (Mammalian Genome, 2023)
The Mouse Phenome Database continues to serve as a curated repository and analysis suite for measured attributes of members of diverse mouse populations. The repository includes annotation to community standard ontologies and guidelines, a database of allelic states for 657 mouse strains, a collection of protocols, and analysis tools for flexible, interactive, user directed analyses that increasingly integrates data across traits and populations. The database has grown from its initial focus on a standard set of inbred strains to include heterogeneous mouse populations such as the Diversity Outbred and mapping crosses and well as Collaborative Cross, Hybrid Mouse Diversity Panel, and recombinant inbred strains. Most recently the system has expanded to include data from the International Mouse Phenotyping Consortium. Collectively these data are accessible by API and provided with an interactive tool suite that enables users’ persistent selection, storage, and operation on collections of measures. The tool suite allows basic analyses, advanced functions with dynamic visualization including multi-population meta-analysis, multivariate outlier detection, trait pattern matching, correlation analyses and other functions. The data resources and analysis suite provide users a flexible environment in which to explore the basis of phenotypic variation in health and disease across the lifespan.

Investigating the effectiveness of Landsat-8 OLI and Sentinel-2 MSI satellite data in monitoring the effects of drought on surface water resources in the Western Cape Province, South Africa - Trisha Deevia Bhaga; Timothy Dube; Munyaradzi Davis Shekede; Cletah Shoko (Remote Sensing Applications: Society and Environment, 2023)

Heightened sensitivity to high-calorie foods in children at risk for obesity: insights from behavior, neuroimaging, and genetics - Kristina M. Rapuano; Link Tejavibulya; Eda Naz Dinc; Anfei Li; Haley Davis; Rachel Korn; Rudolph L. Leibel; B. Timothy Walsh; Lisa Ranzenhofer; Michael Rosenbaum; B. J. Casey; Laurel Mayer (Brain Imaging and Behavior, 2023)
Pediatric obesity is a major public health concern. Genetic susceptibility and increased availability of energy-dense food are known risk factors for obesity. However, the extent to which these factors jointly bias behavior and neural circuitry towards increased adiposity in children remains unclear. While undergoing fMRI, 108 children (ages 5-11y) performed a food-specific go/no-go task. Participants were instructed to either respond (“go”) or inhibit responding (“no-go”) to images of food or toys. Half of the runs depicted high-calorie foods (e.g., pizza) whereas the other half depicted low-calorie foods (e.g., salad). Children were also genotyped for a DNA polymorphism associated with energy intake and obesity ( FTO rs9939609) to examine the influence of obesity risk on behavioral and brain responses to food. Participants demonstrated differences in behavioral sensitivity to high- and low-calorie food images depending on task demands. Participants were slower but more accurate at detecting high- (relative to low-) calorie foods when responding to a neutral stimulus (i.e., toys) and worse at detecting toys when responding to high-calorie foods. Inhibition failures were accompanied by salience network activity (anterior insula, dorsal anterior cingulate cortex), which was driven by false alarms to food images. Children at a greater genetic risk for obesity (dose-dependent model of the FTO genotype) demonstrated pronounced brain and behavioral relationships such that genetic risk was associated with heightened sensitivity to high-calorie food images and increased anterior insula activity. These findings suggest that high-calorie foods may be particularly salient to children at risk for developing eating habits that promote obesity.

Genotoxicity assessment of eight nitrosamines using 2D and 3D HepaRG cell models - Ji-Eun Seo; Joshua Z. Yu; Hannah Xu; Xilin Li; Aisar H. Atrakchi; Timothy J. McGovern; Karen L. Davis Bruno; Nan Mei; Robert H. Heflich; Xiaoqing Guo (Archives of Toxicology, 2023)

Probiotics enhance resistance to Streptococcus iniae in Nile tilapia ( Oreochromis niloticus ) reared in biofloc systems - Uthpala Padeniya; D. Allen Davis; Mark R. Liles; Stacey A. LaFrentz; Benjamin R. LaFrentz; Craig A. Shoemaker; Benjamin H. Beck; Daniel E. Wells; Timothy J. Bruce (Journal of Fish Diseases, 2023)
Biofloc technology is a rearing technique that maintains desired water quality by manipulating carbon and nitrogen and their inherent mixture of organic matter and microbes. Beneficial microorganisms in biofloc systems produce bioactive metabolites that may deter the growth of pathogenic microbes. As little is known about the interaction of biofloc systems and the addition of probiotics, this study focused on this integration to manipulate the microbial community and its interactions within biofloc systems. The present study evaluated two probiotics ( B. velezensis AP193 and BiOWiSH FeedBuilder Syn 3) for use in Nile tilapia ( Oreochromis niloticus ) culture in a biofloc system. Nine independent 3785 L circular tanks were stocked with 120 juveniles (71.4 ± 4.4 g). Tilapia were fed for 16 weeks and randomly assigned three diets: a commercial control diet or a commercial diet top‐coated with either AP193 or BiOWiSH FeedBuilder Syn3. At 14 weeks, the fish were challenged with a low dose of Streptococcus iniae (ARS‐98‐60, 7.2 × 10 7 CFU mL −1 , via intraperitoneal injection) in a common garden experimental design. At 16 weeks, the fish were challenged with a high dose of S. iniae (6.6 × 10 8 CFU mL −1 ) in the same manner. At the end of each challenge trial, cumulative per cent mortality, lysozyme activity and expression of 4 genes ( il‐1β , il6 , il8 and tnfα ) from the spleen were measured. In both challenges, the mortalities of the probiotic‐fed groups were significantly lower ( p S. iniae . Nonetheless, overall il6 expression was lower in fish challenged with a high dose of ARS‐98‐60, while tnfα expression was lower in fish subjected to a lower pathogen dose. Study findings demonstrate the applicability of probiotics as a dietary supplement for tilapia reared in biofloc systems.

Evaluating the diversity of the enigmatic fungal phylum Cryptomycota across habitats using 18S rRNA metabarcoding - C. Alisha Quandt; John A. Marino; D. Rabern Simmons; William J. Davis; Brandon T. Hassett; Kathryn T. Picard; Timothy Y. James (Fungal Ecology, 2023)

Revisiting the mutagenicity and genotoxicity of N-nitroso propranolol in bacterial and human in vitro assays - Xilin Li; Yuan Le; Ji-Eun Seo; Xiaoqing Guo; Yuxi Li; Si Chen; Roberta A. Mittelstaedt; Nyosha Moore; Sharon Guerrero; Audrey Sims; Sruthi T. King; Aisar H. Atrakchi; et al. (Regulatory Toxicology and Pharmacology, 2023)

High abundances of zooxanthellate zoantharians (Palythoa and Zoanthus) at multiple natural analogues: potential model anthozoans? - James Davis Reimer; Sylvain Agostini; Yimnang Golbuu; Ben P. Harvey; Michael Izumiyama; Emmeline A. Jamodiong; Erina Kawai; Hajime Kayanne; Haruko Kurihara; Timothy Ravasi; Shigeki Wada; Riccardo Rodolfo-Metalpa (Coral Reefs, 2023)

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Single-cell technologies uncover intra-tumor heterogeneity in childhood cancers - Yu-Chen Lo; Yuxuan Liu; Marte Kammersgaard; Abhishek Koladiya; Timothy J. Keyes; Kara L. Davis (Seminars in Immunopathology, 2023)

Genotoxicity evaluation of nitrosamine impurities using human TK6 cells transduced with cytochrome P450s - Xilin Li; Xiaobo He; Yuan Le; Xiaoqing Guo; Matthew S. Bryant; Aisar H. Atrakchi; Timothy J. McGovern; Karen L. Davis-Bruno; David A. Keire; Robert H. Heflich; Nan Mei (Archives of Toxicology, 2022)

Opposing global change drivers counterbalance trends in breeding North American monarch butterflies - Michael S. Crossley; Timothy D. Meehan; Matthew D. Moran; Jeffrey Glassberg; William E. Snyder; Andrew K. Davis (Global Change Biology, 2022)
Many insects are in clear decline, with monarch butterflies ( Danaus plexippus ) drawing particular attention as a flagship species. It is well documented that, among migratory populations, numbers of overwintering monarchs have been falling across several decades, but trends among breeding monarchs are less clear. Here, we compile >135,000 monarch observations between 1993 and 2018 from the North American Butterfly Association's annual butterfly count to examine spatiotemporal patterns and potential drivers of adult monarch relative abundance trends across the entire breeding range in eastern and western North America. While the data revealed declines at some sites, particularly the US Northeast and parts of the Midwest, numbers in other areas, notably the US Southeast and Northwest, were unchanged or increasing, yielding a slightly positive overall trend across the species range. Negative impacts of agricultural glyphosate use appeared to be counterbalanced by positive effects of annual temperature, particularly in the US Midwest. Overall, our results suggest that population growth in summer is compensating for losses during the winter and that changing environmental variables have offsetting effects on mortality and/or reproduction. We suggest that density‐dependent reproductive compensation when lower numbers arrive each spring is currently able to maintain relatively stable breeding monarch numbers. However, we caution against complacency since accelerating climate change may bring growing threats. In addition, increases of summer monarchs in some regions, especially in California and in the south, may reflect replacement of migratory with resident populations. Nonetheless, it is perhaps reassuring that ubiquitous downward trends in summer monarch abundance are not evident.

Quantification of microcystin production and biodegradation rates in the western basin of Lake Erie - Justin D. Chaffin; Judy A. Westrick; Elliot Furr; Johnna A. Birbeck; Laura A. Reitz; Keara Stanislawczyk; Wei Li; Peter K. Weber; Thomas B. Bridgeman; Timothy W. Davis; Xavier Mayali (Limnology and Oceanography, 2022)
Cyanobacterial biomass forecasts currently cannot predict the concentrations of microcystin, one of the most ubiquitous cyanotoxins that threaten human and wildlife health globally. Mechanistic insights into how microcystin production and biodegradation by heterotrophic bacteria change spatially and throughout the bloom season can aid in toxin concentration forecasts. We quantified microcystin production and biodegradation during two growth seasons in two western Lake Erie sites with different physicochemical properties commonly plagued by summer Microcystis blooms. Microcystin production rates were greater with elevated nutrients than under ambient conditions and were highest nearshore during the initial phases of the bloom, and production rates were lower in later bloom phases. We examined biodegradation rates of the most common and toxic microcystin by adding extracellular stable isotope‐labeled microcystin‐LR (1 μ g L −1 ), which remained stable in the abiotic treatment (without bacteria) with minimal adsorption onto sediment, but strongly decreased in all unaltered biotic treatments, suggesting biodegradation. Greatest biodegradation rates (highest of −8.76 d −1 , equivalent to the removal of 99.98% in 18 h) were observed during peak bloom conditions, while lower rates were observed with lower cyanobacteria biomass. Cell‐specific nitrogen incorporation from microcystin‐LR by nanoscale imaging mass spectrometry showed that a small percentage of the heterotrophic bacterial community actively degraded microcystin‐LR. Microcystin production and biodegradation rates, combined with the microcystin incorporation by single cells, suggest that microcystin predictive models could be improved by incorporating toxin production and biodegradation rates, which are influenced by cyanobacterial bloom stage (early vs. late bloom), nutrient availability, and bacterial community composition.

Who Gets the Catch? How Conventional Catch Attribution Frameworks Undermine Equity in Transboundary Fisheries - Ruth A. Davis; Quentin Hanich; Bianca Haas; Andrés M. Cisneros-Montemayor; Kamal Azmi; Katherine L. Seto; Wilf Swartz; Pedro C. González-Espinosa; Mathieu Colléter; Timothy J. H. Adams (Frontiers in Marine Science, 2022)
The focus on flag States for the purpose of attributing fisheries catch is inconsistent with the assignment of sovereign rights to coastal States under international law and undermines equity in contemporary quota allocation negotiations. We propose modernizing reporting frameworks to include zone-based reporting of fish catches to more equitably present data, ensure consistency with the Law of the Sea, and better support the realization by developing coastal States of their development aspirations consistent with SDG 14, Life Below Water. States are already required to collect the data necessary to support this change, and many regional fisheries management authorities already do so. Reforms to data collection and reporting mechanisms should support zone-based catch attribution as a central feature of negotiations around access to future fishing opportunities on shared resources. Doing so will ensure that the sovereign rights of developing coastal States are properly accounted for and implemented.

Correction to: Alginate-liposomal construct for bupivacaine delivery and MSC function regulation - Mollie S. Davis; Ileana Marrero-Berrios; Isabel Perez; Timothy Maguire; Palangat Radhakrishnan; Devasena Manchikalapati; Joseph SchianodiCola; Hattiyangangadi Kamath; Rene S. Schloss; Joel Yarmush (Drug Delivery and Translational Research, 2022)

Reproductive success of captive-reared Allegheny Woodrats (Neotoma magister) released into genetically depauperate populations - Miracle M. Davis; Timothy J. Smyser; Scott A. Johnson; Joseph Duchamp; Jeffery L. Larkin; Robert K. Swihart; Jacqueline M. Doyle (Conservation Genetics, 2021)

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)

Lower cardiac output is associated with neurodegeneration among older adults with normal cognition but not mild cognitive impairment - Elizabeth E. Moore; Dandan Liu; Corey W. Bown; Hailey A. Kresge; Deepak K. Gupta; Kimberly R. Pechman; Lisa A. Mendes; L. Taylor Davis; Katherine A. Gifford; Adam W. Anderson; Thomas J. Wang; Bennett A. Landman; et al. (Brain Imaging and Behavior, 2021)

Individual Microcystis colonies harbour distinct bacterial communities that differ by Microcystis oligotype and with time - Derek J. Smith; James Y. Tan; McKenzie A. Powers; Xiaoxia N. Lin; Timothy W. Davis; Gregory J. Dick (Environmental Microbiology, 2021)
Summary Interactions between bacteria and phytoplankton in the phycosphere have impacts at the scale of whole ecosystems, including the development of harmful algal blooms. The cyanobacterium Microcystis causes toxic blooms that threaten freshwater ecosystems and human health globally. Microcystis grows in colonies that harbour dense assemblages of other bacteria, yet the taxonomic composition of these phycosphere communities and the nature of their interactions with Microcystis are not well characterized. To identify the taxa and compositional variance within Microcystis phycosphere communities, we performed 16S rRNA V4 region amplicon sequencing on individual Microcystis colonies collected biweekly via high‐throughput droplet encapsulation during a western Lake Erie cyanobacterial bloom. The Microcystis phycosphere communities were distinct from microbial communities in whole water and bulk phytoplankton seston in western Lake Erie but lacked ‘core’ taxa found across all colonies. However, dissimilarity in phycosphere community composition correlated with sampling date and the Microcystis 16S rRNA oligotype. Several taxa in the phycosphere were specific to and conserved with Microcystis of a single oligotype or sampling date. Together, this suggests that physiological differences between Microcystis strains, temporal changes in strain phenotypes, and the composition of seeding communities may impact community composition of the Microcystis phycosphere.

Unexpected high abundance of aragonite-forming Nanipora (Octocorallia: Helioporacea) at an acidified volcanic reef in southern Japan - James Davis Reimer; Haruko Kurihara; Timothy Ravasi; Yoichi Ide; Michael Izumiyama; Hajime Kayanne (Marine Biodiversity, 2021)

Symbiodiniaceae diversity of Palythoa tuberculosa in the central and southern Red Sea influenced by environmental factors - Hin Boo Wee; Michael L. Berumen; Timothy Ravasi; James Davis Reimer (Coral Reefs, 2020)

Physical drivers facilitating a toxigenic cyanobacterial bloom in a major Great Lakes tributary - Paul G. Matson; Gregory L. Boyer; Thomas B. Bridgeman; George S. Bullerjahn; Douglas D. Kane; Robert M. L. McKay; Katelyn M. McKindles; Heather A. Raymond; Brenda K. Snyder; Richard P. Stumpf; Timothy W. Davis (Limnology and Oceanography, 2020)
The Maumee River is the primary source for nutrients fueling seasonal Microcystis ‐dominated blooms in western Lake Erie's open waters though such blooms in the river are infrequent. The river also serves as source water for multiple public water systems and a large food services facility in northwest Ohio. On 20 September 2017, an unprecedented bloom was reported in the Maumee River estuary within the Toledo metropolitan area, which triggered a recreational water advisory. Here we (1) explore physical drivers likely contributing to the bloom's occurrence, and (2) describe the toxin concentration and bacterioplankton taxonomic composition. A historical analysis using 10‐years of seasonal river discharge, water level, and local wind data identified two instances when high‐retention conditions occurred over ≥ 10 d in the Maumee River estuary: in 2016 and during the 2017 bloom. Observation by remote sensing imagery supported the advection of cyanobacterial cells into the estuary from the lake during 2017 and the lack of an estuary bloom in 2016 due to a weak cyanobacterial bloom in the lake. A rapid‐response survey during the 2017 bloom determined levels of the cyanotoxins, specifically microcystins, in excess of recreational contact limits at sites within the lower 20 km of the river while amplicon sequencing found these sites were dominated by Microcystis . These results highlight the need to broaden our understanding of physical drivers of cyanobacterial blooms within the interface between riverine and lacustrine systems, particularly as such blooms are expected to become more prominent in response to a changing climate.

Reconstructing the climatic niche breadth of land use for animal production during the African Holocene - Leanne N. Phelps; Olivier Broennimann; Katie Manning; Adrian Timpson; Hélène Jousse; Gregoire Mariethoz; Damien A. Fordham; Timothy M. Shanahan; Basil A. S. Davis; Antoine Guisan (Global Ecology and Biogeography, 2020)
Aim Domestic animals first appeared in the archaeological record in northern Africa c. 9000 years before present and subsequently spread southwards throughout the continent. This geographic expansion is well studied and can broadly be explained in terms of the movement of pastoralist populations due to climate change. However, no studies have explicitly evaluated changes in the climatic niche of these domesticates. A priori, one cannot assume a relationship between the geographic spread of animal production and changes in climatic niche breadth because their relationship is highly variable. Therefore, we investigated Holocene changes in the climatic niche of domestic animals (animal production) and compared these to changes in the climatic niche of hunted terrestrial ungulates. Location The African continent. Time period 9000–500 BP. Major taxa studied Domestic animals, hunted (wild) terrestrial ungulates. Methods For the first time, we applied methods from environmental niche dynamics to archaeological data to reconstruct and quantify changes in the climatic niche breadth of animal production during the African Holocene. We used faunal remains from archaeological assemblages and associated radiocarbon dates to estimate the proportion of the African climate space used for animal production and hunting at 500‐year intervals. Results We found that the climatic niche of domestic species broadened significantly with the geographic spread, most notably during the termination of the African Humid Period, whilst no such broadening occurred for the climatic niche of hunted species. Main conclusions Our results provide a quantitative measure of the extent to which humans have constructed and adapted the climatic niche of animal production to manage their domestic animals across increasingly diverse ecological conditions. By incorporating ecological analysis into estimations of past land use, our methods have the potential to improve reconstructions of land use change, and to provide a foundation on which further niche construction hypotheses may be tested.

Species‐specific and temporal scale‐dependent responses of birds to drought - Samantha M. Cady; Timothy J. O'Connell; Scott R. Loss; Nick E. Jaffe; Craig A. Davis (Global Change Biology, 2019)
Global climate change is increasing the frequency and intensity of weather extremes, including severe droughts in many regions. Drought can impact organisms by inhibiting reproduction, reducing survival and abundance, and forcing range shifts. For birds, considering temporal scale by averaging drought‐related variables over different time lengths (i.e., temporal grains) captures different hydrologic attributes which may uniquely influence food supplies, vegetation greenness/structure, and other factors affecting populations. However, studies examining drought impacts on birds often assess a single temporal grain without considering that different species have different life histories that likely determine the temporal grain of their drought response. Furthermore, while drought is known to influence bird abundance and drive between‐year range shifts, less understood is whether it causes within‐range changes in species distributions. Our objectives were to (a) determine which temporal grain of drought (if any) is most related to bird presence/absence and whether this response is species specific; and (b) assess whether drought alters bird distributions by quantifying probability of local colonization and extinction as a function of drought intensity. We used North American Breeding Bird Survey data collected over 16 years, generalized linear mixed models, and dynamic occupancy models to meet these objectives. Different bird species responded to drought at different temporal grains, with most showing the strongest signal at annual or near‐annual grains. For all drought‐responsive species, increased drought intensity at any temporal grain always correlated with decreased occupancy. Additionally, colonization/extinction analyses indicated that one species, the dickcissel ( Spiza americana ), is more likely to colonize novel areas within the southern/core portion of its range during drought. Considering drought at different temporal grains, along with hydrologic attributes captured by each grain, may better reveal mechanisms behind drought impacts on birds and other organisms, and therefore improve understanding of how global climate change impacts species and the landscapes they inhabit.

Considerations in Harmful Algal Bloom Research and Monitoring: Perspectives From a Consensus-Building Workshop and Technology Testing - Beth A. Stauffer; Holly A. Bowers; Earle Buckley; Timothy W. Davis; Thomas H. Johengen; Raphael Kudela; Margaret A. McManus; Heidi Purcell; G. Jason Smith; Andrea Vander Woude; Mario N. Tamburri (Frontiers in Marine Science, 2019)

Ertapenem for osteoarticular infections in obese patients: a pharmacokinetic study of plasma and bone concentrations - Jonathan Chambers; Madhu Page-Sharp; Sam Salman; John Dyer; Timothy M. E. Davis; Kevin T. Batty; Laurens Manning (European Journal of Clinical Pharmacology, 2019)

Early onset of a microcystin-producing cyanobacterial bloom in an agriculturally-influenced Great Lakes tributary - Robert Michael L. Mckay; Taylor Tuttle; Laura A. Reitz; George S. Bullerjahn; William R. Cody; Adam J. McDowell; Timothy W. Davis (Journal of Oceanology and Limnology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Alginate-liposomal construct for bupivacaine delivery and MSC function regulation - Mollie S. Davis; Ileana Marrero-Berrios; Isabel Perez; Timothy Maguire; Palangat Radhakrishnan; Devasena Manchikalapati; Joseph SchianodiCola; Hattiyangangadi Kamath; Rene S. Schloss; Joel Yarmush (Drug Delivery and Translational Research, 2018)

Corrigendum: Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Tom Johengen; Vincent J. Denef; Michelle Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2017)

Genetic control of growth and shoot phenology in juvenile loblolly pine (Pinus taeda L.) clonal trials - Tania Quesada; Liliana M. Parisi; Dudley A. Huber; Salvador A. Gezan; Timothy A. Martin; John M. Davis; Gary F. Peter (Tree Genetics & Genomes, 2017)

An individual-based model of chaparral vegetation response to frequent wildfires - Timothy A. Lucas; Reanna A. Doña; Wancen Jiang; Garrett C. Johns; Dayna J. Mann; Cassandra Seubert; Noah B. C. Webster; Charlotte H. Willens; Stephen D. Davis (Theoretical Ecology, 2017)

Mathematical Modelling of Convection Enhanced Delivery of Carmustine and Paclitaxel for Brain Tumour Therapy - Wenbo Zhan; Davis Yohanes Arifin; Timothy KY Lee; Chi-Hwa Wang (Pharmaceutical Research, 2017)

Cyanobacterial harmful algal blooms are a biological disturbance to Western Lake Erie bacterial communities - Michelle A. Berry; Timothy W. Davis; Rose M. Cory; Melissa B. Duhaime; Thomas H. Johengen; George W. Kling; John A. Marino; Paul A. Den Uyl; Duane Gossiaux; Gregory J. Dick; Vincent J. Denef (Environmental Microbiology, 2017)
Summary Human activities are causing a global proliferation of cyanobacterial harmful algal blooms (CHABs), yet we have limited understanding of how these events affect freshwater bacterial communities. Using weekly data from western Lake Erie in 2014, we investigated how the cyanobacterial community varied over space and time, and whether the bloom affected non‐cyanobacterial (nc‐bacterial) diversity and composition. Cyanobacterial community composition fluctuated dynamically during the bloom, but was dominated by Microcystis and Synechococcus OTUs. The bloom's progression revealed potential impacts to nc‐bacterial diversity. Nc‐bacterial evenness displayed linear, unimodal, or no response to algal pigment levels, depending on the taxonomic group. In addition, the bloom coincided with a large shift in nc‐bacterial community composition. These shifts could be partitioned into components predicted by pH, chlorophyll a , temperature, and water mass movements. Actinobacteria OTUs showed particularly strong correlations to bloom dynamics. AcI‐C OTUs became more abundant, while acI‐A and acI‐B OTUs declined during the bloom, providing evidence of niche partitioning at the sub‐clade level. Thus, our observations in western Lake Erie support a link between CHABs and disturbances to bacterial community diversity and composition. Additionally, the short recovery of many taxa after the bloom indicates that bacterial communities may exhibit resilience to CHABs.

Seasonal Dynamics in Dissolved Organic Matter, Hydrogen Peroxide, and Cyanobacterial Blooms in Lake Erie - Rose M. Cory; Timothy W. Davis; Gregory J. Dick; Thomas Johengen; Vincent J. Denef; Michelle A. Berry; Sarah E. Page; Susan B. Watson; Kate Yuhas; George W. Kling (Frontiers in Marine Science, 2016)

NMR-Based Metabolomics Separates the Distinct Stages of Disease in a Chronic Relapsing Model of Multiple Sclerosis - Alex M. Dickens; James R. Larkin; Benjamin G. Davis; Julian L. Griffin; Timothy D. W. Claridge; Nicola R. Sibson; Daniel C. Anthony (Journal of Neuroimmune Pharmacology, 2015)

EGFR Targeted Theranostic Nanoemulsion for Image-Guided Ovarian Cancer Therapy - Srinivas Ganta; Amit Singh; Praveen Kulkarni; Amanda W. Keeler; Aleksandr Piroyan; Rupa R. Sawant; Niravkumar R. Patel; Barbara Davis; Craig Ferris; Sara O’Neal; William Zamboni; Mansoor M. Amiji; et al. (Pharmaceutical Research, 2015)

Erratum to: Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; John Blangero; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Multi-region hemispheric specialization differentiates human from nonhuman primate brain function - Hsiao-Ying Wey; Kimberley A. Phillips; D. Reese McKay; Angela R. Laird; Peter Kochunov; M. Duff Davis; David C. Glahn; Timothy Q. Duong; Peter T. Fox (Brain Structure and Function, 2014)

Development of EGFR-Targeted Nanoemulsion for Imaging and Novel Platinum Therapy of Ovarian Cancer - Srinivas Ganta; Amit Singh; Niravkumar R. Patel; Joseph Cacaccio; Yashesh H. Rawal; Barbara J. Davis; Mansoor M. Amiji; Timothy P. Coleman (Pharmaceutical Research, 2014)

Validation of PyMBMS as a High-throughput Screen for Lignin Abundance in Lignocellulosic Biomass of Grasses - Bryan W. Penning; Robert W. Sykes; Nicholas C. Babcock; Christopher K. Dugard; John F. Klimek; David Gamblin; Mark Davis; Timothy R. Filley; Nathan S. Mosier; Clifford F. Weil; Maureen C. McCann; Nicholas C. Carpita (BioEnergy Research, 2014)

Breeding for value in a changing world: past achievements and future prospects - Tim White; John Davis; Salvador Gezan; Jiri Hulcr; Eric Jokela; Matias Kirst; Timothy A. Martin; Gary Peter; Greg Powell; Jason Smith (New Forests, 2014)

The association between neighborhood socioeconomic status and ovarian cancer tumor characteristics - Caryn E. Peterson; Garth H. Rauscher; Timothy P. Johnson; Carolyn V. Kirschner; Richard E. Barrett; Seijeoung Kim; Marian L. Fitzgibbon; Charlotte E. Joslin; Faith G. Davis (Cancer Causes & Control, 2014)

Carbon storage in tropical forests correlates with taxonomic diversity and functional dominance on a global scale - Kyle C. Cavanaugh; J. Stephen Gosnell; Samantha L. Davis; Jorge Ahumada; Patrick Boundja; David B. Clark; Badru Mugerwa; Patrick A. Jansen; Timothy G. O'Brien; Francesco Rovero; Douglas Sheil; Rodolfo Vasquez; et al. (Global Ecology and Biogeography, 2014)
Aim We examined (1) the relationships between aboveground tropical forest C storage, biodiversity and environmental drivers and (2) how these relationships inform theory concerning ecosystem function and biodiversity. Experiments have shown that there is a positive relationship between biodiversity and ecosystem functioning, but intense debate exists on the underlying mechanisms. While some argue that mechanisms such as niche complementarity increase ecosystem function, others argue that these relationships are a selection effect. Location Eleven tropical forests in the A mericas, A frica and A sia. Methods We analysed the correlates of biodiversity and carbon storage in tropical forests using data from 59 1‐ha tree plots from a standardized global tropical forest biodiversity‐monitoring network. We examined taxonomic and functional diversity, aboveground C storage and environmental variables in order to determine the relationships between biodiversity and carbon storage in natural (non‐plantation) tropical forests. Results We found that aboveground C storage in tropical forests increased with both taxonomic diversity and functional dominance, specifically the dominance of genera with large maximum diameters, after potential environmental drivers were accounted for (final model R 2 = 0.38, P Main conclusions Our results suggest that niche complementarity and the selection effect are not mutually exclusive: they both play a role in structuring tropical forests. While previous studies have documented relationships between diversity and C storage, these have largely been conducted on small scales in biomes that are relatively species poor compared with tropical forests (e.g. grasslands and temperate or boreal forests). Our results demonstrate that these positive biodiversity–ecosystem functioning relationships are also present in hyperdiverse systems on spatial scales relevant to conservation and management. This insight can be used to inform the conservation and management of tropical forests, which play a critical role in the global carbon cycle and are some of the biologically richest ecosystems on the planet.

Increased dietary sodium induces COX2 expression by activating NFκB in renal medullary interstitial cells - Wenjuan He; Min Zhang; Min Zhao; Linda S. Davis; Timothy S. Blackwell; Fiona Yull; Matthew D. Breyer; Chuan-Ming Hao (Pflügers Archiv - European Journal of Physiology, 2014)

Acute hyperglycaemia does not alter nitric oxide-mediated microvascular function in the skin of adolescents with type 1 diabetes - Louise H. Naylor; Norhaida M. Yusof; Nirubasini Paramalingam; Timothy W. Jones; Elizabeth A. Davis; Daniel J. Green (European Journal of Applied Physiology, 2014)

Characterization of Recombinant Human IL-15 Deamidation and Its Practical Elimination through Substitution of Asparagine 77 - David F. Nellis; Dennis F. Michiel; Man-Shiow Jiang; Dominic Esposito; Richard Davis; Hengguang Jiang; Angela Korrell; George C. Knapp; Lauren E. Lucernoni; Roy E. Nelson; Emily M. Pritt; Lauren V. Procter; et al. (Pharmaceutical Research, 2012)

Pacific Rim Forestry - Thomas Brandeis; Olaf Kuegler; Robert Pattison; Örjan Jonsson; James Halperin; Kathleen McGinely; Constance Carpenter; Kathleen Friday; Guy Robertson; Nicklos Dudley; Robert James; Richard Sniezko; et al. (Journal of Forestry, 2011)
68Stakeholders' questions about subtropical and tropical forests can be as diverse and unique as the forests themselves. Obtaining the information needed to begin answering these questions requires innovation and adaptation of existing forest mensuration and inventory techniques that were developed primarily for use in temperate and boreal forests with a strong forest industry presence. Five cycles of forest inventory and monitoring in Puerto Rico and two cycles in the US Virgin Islands under the Forest Inventory and Analysis (FIA) program highlight the commonalities and differences between working in these subtropical forests and the temperate forests of the continental United States. Additionally, the Caribbean implementation of the FIA program has often taken a different approach from that used in the Pacific Islands territories. We can improve on delivery of forest resource information to island stakeholders by studying these experiences. By sharing the lessons learned with other Pacific Rim countries engaging in forest inventory and monitoring, we can learn from each other.

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Two new combinations in Pyrostria (Rubiaceae, Vanguerieae) from Thailand - Timothy M. A. Utteridge; Aaron P. Davis (Kew Bulletin, 2009)

Role of Convective Flow in Carmustine Delivery to a Brain Tumor - Davis Yohanes Arifin; Kam Yiu Timothy Lee; Chi-Hwa Wang; Kenneth A. Smith (Pharmaceutical Research, 2009)

Impact of geography on mammography use in California - Monica C. Jackson; William W. Davis; William Waldron; Timothy S. McNeel; Ruth Pfeiffer; Nancy Breen (Cancer Causes & Control, 2009)

A high-resolution geophysical investigation of sediment distribution controlled by catchment size and tides in a multi-basin turbid outwash fjord: Simpson Bay, Prince William Sound, Alaska - Christian J. Noll; Timothy M. Dellapenna; Andrea Gilkinson; Randall W. Davis (Geo-Marine Letters, 2009)

Inheritance of foliar stable carbon isotope discrimination and third-year height in Pinus taeda clones on contrasting sites in Florida and Georgia - Brian S. Baltunis; Timothy A. Martin; Dudley A. Huber; John M. Davis (Tree Genetics & Genomes, 2008)

Comparative genomics reveals functional transcriptional control sequences in the Prop1 gene - Robert D. Ward; Shannon W. Davis; MinChul Cho; Constance Esposito; Robert H. Lyons; Jan-Fang Cheng; Edward M. Rubin; Simon J. Rhodes; Lori T. Raetzman; Timothy P. L. Smith; Sally A. Camper (Mammalian Genome, 2007)

Genetic dissection of fusiform rust and pitch canker disease traits in loblolly pine - Gogce C. Kayihan; Dudley A. Huber; Alison M. Morse; Timothy L. White; John M. Davis (Theoretical and Applied Genetics, 2005)

A prevalent POLG CAG microsatellite length allele in humans and African great apes - Anja T. Rovio; Josef Abel; Arja L. Ahola; Aida M. Andres; Jaume Bertranpetit; Antoine Blancher; Ronald E. Bontrop; Leona G. Chemnick; Howard J. Cooke; James M. Cummins; Heidi A. Davis; David J. Elliott; et al. (Mammalian Genome, 2004)

Freeze/thaw stress in Ceanothus of southern California chaparral - Frank W. Ewers; Michael C. Lawson; Timothy J. Bowen; Stephen D. Davis (Oecologia, 2003)

Book reviews - Gerard L. Coté; Nasreen Haideri; Yadin David; William A. Hyman; Roy B. Davis; Benjamin S. Kelley; Timothy W. King (Annals of Biomedical Engineering, 1992)